SEVILLA and U.M. LUSTRIA. 2006. Changes in rumen ecosystem and feed dry matter degradability of buffalo which received rumen content of cattle through cross inoculation - Pamungkas, Dicky; Sevilla, Cesar C; Lustria, Ulysses M (Indonesian Animal Sciences Society, 2006)
The research was done to identify changes in rumen ecosystem of buffalo which received rumen content of cattle. As much as three head of fistulated male buffaloes (live weight of 450-550 kg) and three fistulated female cattle (live weight 250-380 kg) were used. This experiment was done three stage as follows: pre-inoculation, inoculation and post-inoculation. In Pre-inoculation, the sample of rumen content was taken two hours before morning feeding and directly observed for pH rumen liquor, ammonia nitrogen (NH3-N) and total volatile fatty acid (VFA). During the last three days of the first week of pre and post inoculation, the in situ dry matter digestibility was conducted. The samples were incubated for 0, 3, 6, 9, 12, 24, 48, and 72 hours in the rumen of the experimental animals. Napier grass, leucaena, and wheat pollard were incubated separately in the nylon bags to determine DM digestibility. The cross inoculation (total of rumen content) was done less than 10 minutes. In post-inoculation, the sample of rumen content was taken at two hours before morning feeding as long as two days of two weeks after inoculation. Changes in rumen ecosystem (pH, NH3-N and total VFA) were tested by using Completely Randomized Design. Result showed that the transfer of rumen content from cattle to buffalo significantly reduced the pH level in the rumen of buffalo. However, it had no significant effect on the ammonia concentration in the rumen of buffalo and showed significantly decreased of bacteria but it was not affect on the total count of protozoa and fungi. The transfer of rumen content from cattle to buffalo significantly decreased the value of insoluble and potential digestible fraction of leucaena. The DM effective degradability of Napier grass was significantly increase (P<0.05) within outflow rate 0.02 and 0.04 h-1 after cross inoculation. In wheat pollard, a significantly decrease (P<0.05) was occurred when outflow rate was observed at 0.04, 0.06 and 0.08 h-1 Key Words: Rumen Ecosystem, Cross Inoculation, Degradability